Education and indoor smoking among parents who smoke: the mediating role of perceived social norms of smoking - Junko Saito; Akira Shibanuma; Junko Yasuoka; Naoki Kondo; Daisuke Takagi; Masamine Jimba (BMC, 2018)
Abstract Background Parents with less formal education are more likely to smoke indoors, causing socioeconomic disparity in children's exposure to second-hand smoke. However, little is known about the roles of social factors in the socioeconomic gradients of indoor smoking. We tested the potential mediating role of perceived smoking norms on the associations between education and indoor smoking among parents who smoke. Methods In this cross-sectional study, 822 smoking fathers and 823 smoking mothers, who lived with young children and were members of a Japanese online survey panel, participated. Structural equation modelling tested the mediating effects of perceived descriptive and subjective norms on the association between education and indoor smoking. Results Perceived pro-smoking norms, which were more prevalent among less-educated parents, mediated the association between education and indoor smoking. Household smoking status and worksite smoking ban also mediated this association via perceived norms, but only for fathers. Perceived descriptive norms explained 28.5% of the association for fathers and 37.6% for mothers; the corresponding percentages for perceived subjective norms were 9.8% and 26.6%, respectively. Conclusions Perceived smoking norms, household smoking status, and a worksite smoking ban could be vital targets of a strategy aimed at reducing the socioeconomic disparity in parental home smoking behaviours.